Development of prebiotic galactooligosaccharide enriched buttermilkand evaluation of its storage stability: Prebiotic Galactooligosaccharide Enriched Buttermilk - Tahir, Hafsa; Bacha, Umar; Iqbal, Sanaullah; Iqbal, Syeda Saira; Tanweer, Afifa (Progress in Nutrition, 2019)
Prebiotic Galacto-oligosacchrides (GOS) is reportedly present in human milk and elicits bacterial growth i.e. beneficial bacteria in human intestines. The aim of the present study was to produce GOS through trans-galactosylation and development of GOS based buttermilk. Trans-galactosylation process was carried out in pasteurized milk (100 ºC) to produce prebiotic GOS. Yogurt was produced from GOS containing milk and then after the churning of yogurt buttermilk was produced from trans-glycosylated milk.Results showed that, enzyme concentration between 400-600µL/5ml can produce GOS in 30min and 1hr samples. Chemical analysis and sensory evaluation of plain/control and GOS containing buttermilk showed no remarkable difference. While shelf life study showed that there was no significant difference between the overall quality of buttermilk in glass and pouch packaging. Buttermilk in pouch packaging maintained its stability for 6 days without adding any kind of preservative.